ANALISIS KUALITAS SUMBER DAYA MANUSIA BAGIAN AKUNTANSI DALAM PEMAHAMAN TERHADAP LAPORAN KEUANGAN PADA BUMD KOTA BANDUNG - Sukiati, Wiwin; Surya Fauzia Pertami, Yuli (Program Studi Akuntansi FPEB UPI, 2017)
The goal is to determine the extent of the rules on preparation of financial statements have been understood and applied in BUMD Bandung, andÂ factors that inhibit good quality financial reports can be achieved. The purpose of this research is to identify the quality of human resources in accounting department to understand and prepare the financial statements in order to achieve good quality financial reports, and to determine factors that inhibit good quality financial reports can be achieved. By using linear regression analysis method, it is known that the human resources have a significant effect on the quality of financial reporting information. It is supported by the results of direct interviews that the limiting factors in producing the quality of financial reporting information is the number of human resources in accounting department are inadequate, and the lack of knowledge about the science of accounting.